The problem of pensions in Colombia (2014)
This essay aims to show that Colombia has deficiencies in the General Pension System, considering that currently coexist two regimes having different as one of private properties and other public, this condition has led to the submission pronounced a gap between the value of the collection and the value paid for countertops current and projected future pension in RPM. These financial problems that today result in gaps in coverage, prompted the government to search through recent reforms to extend the retirement age, the weeks of contributions and reducing benefits among others.